Genome-Wide Analysis of DNA Methylation During Ovule Development of Female-Sterile Rice fsv1. Issue 11 (1st November 2017) - Liu, Helian; Wu, Ya; Cao, Aqin; Mao, Bigang; Zhao, Bingran; Wang, Jianbo
Abstract: The regulation of female fertility is an important field of rice sexual reproduction research. DNA methylation is an essential epigenetic modification that dynamically regulates gene expression during development processes. However, few reports have described the methylation profiles of female-sterile rice during ovule development. In this study, ovules were continuously acquired from the beginning of megaspore mother cell meiosis until the mature female gametophyte formation period, and global DNA methylation patterns were compared in the ovules of a high-frequency female-sterile line ( fsv1 ) and a wild-type rice line (Gui99) using whole-genome bisulfite sequencing (WGBS). Profiling of the global DNA methylation revealed hypo-methylation, and 3471 significantly differentially methylated regions (DMRs) were observed in fsv1 ovules compared with Gui99. Based on functional annotation and Kyoto encyclopedia of genes and genomes (KEGG) pathway analysis of differentially methylated genes (DMGs), we observed more DMGs enriched in cellular component, reproduction regulation, metabolic pathway, and other pathways. In particular, many ovule development genes and plant hormone-related genes showed significantly different methylation patterns in the two rice lines, and these differences may provide important clues for revealing the mechanism of female gametophyte abortion.